Experiences from Ground, Coastal and Transitional Water Quality Monitoring The EU Water Framework Directive Implementation in the Catalan River Basin District (Part II) - Munné, Antoni; Ginebreda, Antoni; Prat, Narcís (The Handbook of Environmental Chemistry,, 2016)
This book details the experiences gained by the Catalan Water Agency (ACA) in a Mediterranean watershed - the Catalan River Basin District - following the launch of the EU Water Framework Directive (WFD) in the year 2000. Groundwater and coastal water experts present 13 chapters defining tools for water-status assessment specially adapted to Mediterranean conditions. The content of this and the companion volume Experiences from Surface Water Quality Monitoring: The EU Water Framework Directive Implementation in the Catalan River Basin District (Part I) are the result of an excellent collaboration between the ACA and several Catalan universities and research centers to cope with new challenges provided by the WFD monitoring requirements. The volume serves as a useful guide for environmental managers and scientists engaged in other European as well as Non-European river basins. .